Hz. Peygamber'den Emevîlerin Sonuna Kadar Hac Kafilelerinin Güzergâhları - Ataş, Haci (Muş Alparslan Üniversitesi, 2021)
Mecca and Medina, accepted as “Haremeyn”, are privileged cities in terms of Islamic History. Islam was born and developed in these two cities and spread to the world from here. The fact that Mecca includes the Kaaba, the qibla of Muslims, has caused millions of Muslims to visit this place every year for the purpose of hajj and umrah. Medina, which hosted the tomb of the Prophet Muhammad (pbuh), became the second city to be visited for religious reasons after his death. The transfer of the state center outside the Hijaz during the Umayyad and Abbasid period did not eliminate the influence of these cities. The pilgrimage ceremonies held in Mecca and Medina are of great importance in the continuation of this influence. As a result of this importance, hundreds of pilgrimage convoys flocked to Mecca from various parts of the world, risking arduous journeys. The journey of pilgrimage convoys, which reached hundreds of kilometers and lasted for months in the first periods of Islam, also led to the emergence of an independent institution. For this purpose, an institution was established with the name of "Pilgrimage Emirate", whose most important task is to safely take pilgrimage convoys to holy places and re-bring them. Since the transportation of the pilgrimage convoys to the holy places by the shortest and safest ways brought an important responsibility, the caliphs either carried out this delicate task themselves or handed it over to the names they trusted the most. In this study, the routes followed by the pilgrimage convoys to Mecca under the presidency of the pilgrimage emiraters are handled. Our study is limited to the date range starting from the period of the Prophet Muhammad (pbuh) when the first pilgrimage convoy started and continuing until the end of the Umayyads.

Haremeyn olarak kabul edilen Mekke ve Medine, İslâm tarihi açısından ayrıcalıklı şehirlerdendir. İslâmiyet Mekke’de doğmuş, Medine’de gelişmiş ve dünyaya da buralardan yayılmıştır. Mekke’nin, Müslümanların kıblesi Kâbe’yi bünyesinde barındırması her yıl milyonlarca Müslümanın hac ve umre amacıyla burayı ziyaret etmesini sağlamıştır. Hz. Peygamber’in kabrini misafir eden Medine de onun vefatından sonra dinî saiklerle ziyaret edilen ikinci şehir olmuştur. Emevîler ve Abbasîler döneminde devlet merkezinin Hicaz’ın dışına taşınması bu şehirlerin etkisini ortadan kaldırmamıştır. Bu tesirin devam etmesinde Mekke ve Medine’ye düzenlenen hac merasimlerinin ehemmiyeti oldukça fazladır. Bu ehemmiyetin sonucunda yüzlerce hac kafilesi meşakkatli yolculukları göze alarak dünyanın çeşitli bölgelerinden Mekke’ye akın etmiştir. İslâm’ın ilk dönemlerinde yüzlerce km’yi bulan ve aylarca süren hac kafilelerinin yolculuğu müstakil bir kurumun ortaya çıkmasını da sağlamıştır. Bu amaçla “Hac Emirliği” adıyla, en önemli görevi, hac kafilelerini güvenli bir şekilde kutsal mekânlara götürüp getirmek olan bir kurum ihdas edilmiştir. Hac kafilelerinin en kısa ve en güvenli yollardan kutsal mekânlara götürülmesi önemli bir sorumluluk getirdiğinden halifeler, bu hassas vazifeyi ya kendileri bizzat yürütmüşler ya da en güvendikleri isimlere bu görevi tevdi etmişlerdir. Bu çalışmada hac emirlerinin başkanlığında Mekke’ye giden hac kafilelerinin takip ettikleri güzergâhlar ele alınmıştır. Çalışmamız, ilk hac kafilesinin yola çıktığı Hz. Peygamber döneminden başlayıp Emevîlerin sonuna kadar devam eden tarih aralığı ile sınırlandırılmıştır.
The Routes of the Hajj Convoys from the Prophet Muhammad (pbuh) to the End of the Umayyads
dinbil
Keywords: Islamic History; Hajj Convoy; Hajj Emirate; Mecca; Route.; İslâm Tarihi; Hac kafilesi; Hac Emirliği; Mekke; Güzergâh.